A Study of the Impact of Artificial Intelligence on Consumer Decision Making - Dmitrievich, Shmatko Aleksey; Anatolyevna, Volkova Anastasia; Nurmagomedovich, Rasulov Zainodin; Yuryevich, Remshev Evgeny; Ivanovich, Olekhver Aleksey (Journal of Ecohumanism, 2024)
The article considers not only the obvious benefits of using AI, but also potential risks associated with changing consumer behavior. The study introduces the User Engagement Index (UEI), which allows measuring and comparing user activity and interaction with marketplaces, considering the influence of AI. The proposed methodology can become the basis for further research in the field of human-artificial intelligence interaction in the digital environment. The UEI formula allows for a comprehensive assessment of user engagement, considering several key factors that influence user behavior on the site.